Les cinémas indépendants comme espaces de vie sociale, culturelle et citoyenne en Seine-Saint-Denis - Charles Marques (Territoire en Mouvement)
The cinema can be understood through multiple aspects: art, a machine or a space. The cinematographic space is a social space where the community shares a common experience. The French state initiated a public aid system who made what we refer as « french cultural exception ». The french theaters are divided in multiple categories: from the art et essai theater to the blockbuster theater, from public cinema owned by the town hall to the multiplex owned by a private company. This article is about, based on interviews, the public theaters, owned by the city or an association depending on the city fundings, and the cultural policies initiated in Seine-Saint-Denis to transform the projection into a social, cultural and citizen activity.